Role of Nutritive Factors in Infants Sleep Management - Tatiana V. Turti; Irina A. Belyaeva; Elena P. Bombardirova; Pavel E. Sadchikov; Alexander Y. Nagonov (Вопросы современной педиатрии)
The organized infant’s sleep schedule is the crucial part of normal individual development. On the contrary, restless sleep, nocturnal awakening, long wakefulness can lead to deviations in physical, psychomotor, and cognitive development. Feeding schedule organized according to the time of a day and circadian rhythms (chrono-nutrition concept) can be useful for prevention and correction of such disorders. You are aware of the effect of such factors as feeding before night's sleep, nutrition at dark time of a day, diet enriched with triptophane and nucleotides, on the maturation and consolidation of infants sleep. The correlation between intestinal microbiota and factors affecting the circadian and metabolic activity of the body are presented: day-night cycles, sleep and wake, diet and nutrition. Targeted regulation of the intestinal microbiota through products enriched with functional components (prebiotics) can lead to the development of healthy sleep in infants via axis “brain - intestine - microbiota".